2021
DOI: 10.1017/s0959270921000228
|View full text |Cite
|
Sign up to set email alerts
|

Priority areas for vulture conservation in the Horn of Africa largely fall outside the protected area network

Abstract: Summary Vulture populations are in severe decline across Africa and prioritization of geographic areas for their conservation is urgently needed. To do so, we compiled three independent datasets on vulture occurrence from road-surveys, GPS-tracking, and citizen science (eBird), and used maximum entropy to build ensemble species distribution models (SDMs). We then identified spatial vulture conservation priorities in Ethiopia, a stronghold for vultures in Africa, while accounting for uncertainty in our predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 73 publications
(161 reference statements)
0
10
1
Order By: Relevance
“…Our preliminary results thus reaffirm the critical contribution of protected areas to the conservation of critically endangered African vulture species (Murn et al, 2016 ; Salewski, 2021 ; Xirouchakkis & Mylonas, 2007 ). Our results are, however, contrary to findings from other studies which showed that some vulture species tend to prefer human‐dominated landscapes compared to protected areas, thus posing several conservation challenges to wildlife managers (Buechley et al, 2021 ; Henriques et al, 2018 ; Phipps et al, 2013 ). Such vultures could probably be attracted by sporadic food sources found in human landscapes (Murn & Anderson, 2008 ; Phipps et al, 2013 ).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our preliminary results thus reaffirm the critical contribution of protected areas to the conservation of critically endangered African vulture species (Murn et al, 2016 ; Salewski, 2021 ; Xirouchakkis & Mylonas, 2007 ). Our results are, however, contrary to findings from other studies which showed that some vulture species tend to prefer human‐dominated landscapes compared to protected areas, thus posing several conservation challenges to wildlife managers (Buechley et al, 2021 ; Henriques et al, 2018 ; Phipps et al, 2013 ). Such vultures could probably be attracted by sporadic food sources found in human landscapes (Murn & Anderson, 2008 ; Phipps et al, 2013 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Albeit providing key ecological functions, their populations have continued to decline severely due to several threats such as poisoning, habitat loss, shortage of food, collision with infrastructural facilities such as power lines, as well as from persecution (Buechley & Şekercioğlu, 2016 ; Gilbert et al, 2006 ; Margalida & Ogada, 2018 ; Ogada et al, 2016 ; Safford et al, 2019 ; Thorley & Clutton‐Brock, 2017 ). It is in this context that conservation of vultures is now considered a top priority at a global scale (Buechley et al, 2019 , 2021 ; Safford et al, 2019 ). One of the overarching challenges facing efforts to priorities vulture conservation is lack of spatially explicit knowledge regarding the distribution of key overlapping geographic zones and habitats supporting vulture populations in terms of food predictability as well as secure breeding and roosting sites (Buechley et al, 2019 ; Reading et al, 2019 ; Salewski, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, detection rates of facultative scavengers, including dogs, The detected decline in vultures feeding at abattoirs in the study is concerning, given that it consisted of white-backed, Rüppell's, and hooded vultures, all 3 of which are globally critically endangered (BirdLife International 2021). These species are experiencing population declines across Africa (Ogada et al 2016) and Ethiopia is regarded as an important stronghold for them, in large part because of the reliable food source that abattoirs provide in the country (Botha et al 2017, Buechley et al 2021. The observed decline in vulture detections in this study cannot definitively be contributed to population declines.…”
Section: Discussionmentioning
confidence: 67%
“…As wild animals and their respective carcasses become scarcer, vultures increasingly rely on feeding on livestock carcasses and at abattoirs and dump sites (López-López et al 2014, Tauler-Ametlller et al 2019. This is certainly the case in Ethiopia (Hibste and Bekele 2007;Buechley et al 2018Buechley et al , 2021. As the second most populous country in Africa (United Nations 2017), most Ethiopian landscapes are dominated by humans and associated livestock, with livestock outnumbering wildlife even in national parks (Stephens et al 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation